British design : tradition and modernity after 1948 - Breward, Christopher, 1965-; Fisher, Fiona; Wood, Ghislaine (Bloomsbury Academic, 2015)
"British Design brings together a collection of essays from international scholars, designers and journalists, offering new perspectives on the significance of British design in the last sixty years. The book reacts and responds to the changes that have taken place in the recent history of British Design, with case studies looking at, among others, domestic interiors, retail spaces, schools, universities and objects of transport. Chapters include investigations into a variety of significant historical and social moments from the rise and fall of the English Country House style and the Brutalist architectural boom of the 1960s to the modern shopping space and key contemporary designers such as Thomas Heatherwick. British Design provides the contemporary study of the developments within British design and provides new criticism and analysis on how design, from post-war Britain to today, has developed and changed how we live and interact with the spaces in which we live"--